Peran Environmental Sustainability Disclosure Sebagai Mediator Antara Akuntansi Lingkungan Terhadap Kinerja Perusahaan - Ronald Wangdra; Viola Syukrina E Janrosl; Suvianto Wangdra (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
Companies today in carrying out business activities are required not only to be able to create material profits but also to be able to pay attention to the environment whose results will later have an impact on the company's performance. The problem in this study is that there are many companies that do not pay attention to the environment, especially the mining sector, as evidenced by the fact that there are still many companies in the mining sector that achieve low proper and there are still many companies that do not present environmental costs in the company's financial statements. Based on data obtained from the proper rating of the Ministry of Environment for 34 coal mining companies listed on the IDX, as many as 4 companies are rated black and the remaining 30 companies are rated red and green, indicating that the company ignores the environment when making profits. This study aims to analyze whether environmental accounting and audit quality affect company performance as well as the influence of mediation of environmental sustainability disclosure on environmental accounting and audit quality on the performance of mining companies listed on the Indonesia Stock Exchange in 2018-2022.The analysis method used is a quantitative method with a causality or causal approach. Data analysis using a statistical tool, namely Smart PLS. The results of this study are that audit quality and environmental accounting have a significant effect on company performance, audit quality has a significant effect on environmental sustainability disclosure. However, environmental accounting does not have a significant effect on environmental sustainability disclosure. Then environmental sustainability disclosure does not have a significant effect on company performance. Mediation testing shows that quality audits indirectly significantly affect company performance through environmental sustainability disclosure. Environmental sustainability disclosure significance mediates the relationship between environmental accounting and company performance.